Serum Endocan Levels on Admission Are Associated With Worse Clinical Outcomes in COVID-19 Patients: A Pilot Study. (February 2021) - Medetalibeyoglu, Alpay; Emet, Samim; Kose, Murat; Akpinar, Timur Selcuk; Senkal, Naci; Catma, Yunus; Kaytaz, Arif Murat; Genc, Sema; Omer, Beyhan; Tukek, Tufan
Thrombotic and embolic complications in the cardiovascular system are evident and associated with worse prognosis in coronavirus disease 2019 (COVID-19) patients. Endothelial-specific molecule 1 (endocan) plays a role in vascular pathology. We hypothesized serum endocan levels on admission are associated with primary composite end point (mortality and intensive care unit hospitalization) in COVID-19 patients. Patients (n = 80) with laboratory, clinical, and radiological confirmed COVID-19 were included in this cross-sectional study. Ten milliliter of peripheral venous blood were drawn within 24 hours of admission to estimate serum endocan levels. Data were analyzed using SPSS version 26.0 (IBM). Patients with the primary composite end point had significantly higher serum endocan levels than patients without (852.2 ± 522.7 vs 550.2 ± 440.8 ng/L, respectively; P < .01). In the logistic regression analysis, only increased serum endocan levels and increase in age were independent predictors of the primary composite end point ( P < .05). In the receiver operating characteristics curve analysis, we found that a serum endocan level of 276.4 ng/L had a 97% sensitivity and 85% specificity for prediction of the primary composite end point. Baseline serum endocan levels may prove useful as a prognostic factor in patients hospitalized for COVID-19.